Genetic structure and diversity in Brazilian populations of Anastrepha obliqua (Diptera: Tephritidae) - Passos, Joseane F.; Nascimento, Danilo Baia do; Menezes, Rodolpho Santos Telles; Araujo, Elton Lucio; Lima, Kátia Manuela; Zucchi, Roberto Antonio; Teles, Beatriz Ronchi; Nascimento, Ruth R.do; Arce, Raul Ruiz; Barr, Norman B.; Mcpheron, Bruce A.; Silva, Janisete Gomes (PLoS ONE, 2018)
Anastrepha obliqua (Macquart), the West Indian fruit fly, is one of the most economically important pest species in the Neotropical region. It infests an extensive range of host plants that include over 60 species. The geographic range of A. obliqua is from northern Mexico to southern Brazil and includes the Caribbean Islands. Previous molecular studies have revealed significant genetic structure among populations. We used sequences from a fragment of the mitochondrial protein-coding gene cytochrome c oxidase I to estimate structure and genetic diversity of A. obliqua populations from Brazil. We analyzed a total of 153 specimens from the Amazon Forest, Atlantic Forest, Cerrado, and Caatinga biomes. Our study revealed weak genetic structure among the A. obliqua Brazilian populations sampled. Collections from the Amazon Forest had similar haplotype diversity compared to previously reported estimates for collections from the Caribbean and both populations are also closely related to each other, thus challenging the hypothesis that A. obliqua originated in the Caribbean and then moved to other regions of the Americas. Therefore, further evidence is necessary to draw a definite conclusion about the putative center of origin for A. obliqua. Additionally, we suggest a putative historical migration from the west to the east for the A. obliqua Brazilian populations, which could explain the high genetic diversity for this fly in the Amazon Forest and low genetic diversity in the other Brazilian biomes. © Copyright: This is an open access article, free of all copyright, and may be freely reproduced, distributed, transmitted, modified, built upon, or otherwise used by anyone for any lawful purpose. The work is made available under the Creative Commons CC0 public domain dedication.
Keywords: Cytochrome C Oxidase; Mitochondrial Protein; Dna, Mitochondrial; Amazonas; Anastrepha Obliqua; Biome; Brazilian; Caribbean Islands; Diptera; Gene Structures; Genetic Variability; Haplotype; Insect Genetics; Nonhuman; Population Migration; Scrub; Tephritidae; United States; Animals; Animals Dispersal; Biodiversity; Forest; Gene Structures; Genetics; Phylogeny; Animals Distribution; Animalss; Biodiversity; Dna, Mitochondrial; Forests; Genetic Structures; Phylogeny; Tephritidae